Inter-campus comparison of undergraduates’ health literacy and associated factors in Universiti Sains Malaysia (USM) - Zhen, Tee Hong (Universiti Sains Malaysia, 2024)
Health literacy is the ability to seek, understand, evaluate and act on health information in three subdomains of healthcare, disease prevention and health promotion. Many studies have shown that poor levels of health literacy are associated with poor health outcomes. This study sought to determine and compare health literacy among USM’s Main Campus, Health Campus and Engineering Campus, and identify the presence of association between selected sociodemographic characteristics and self-esteem with health literacy. To that end, this study utilised a cross-sectional study design and respondents were recruited via social media applications. An explanation of the study and a link to a Google form containing the questionnaire were given. A total of 357 responses were obtained. Descriptive statistics were used to describe the respondents and obtain the level of health literacy they have, one-way ANOVA was used to compare health literacy among campuses, and Pearson’s Chi-Square test was used to determine the presence of associations between selected sociodemographic characteristics and self-esteem with health literacy. Study results indicated that health literacy among undergraduates is moderate (mean index score of 33.85 out of 50) and that close to half the respondents (44.3%) had limited health literacy. It also showed that respondents from the Health Campus had better health literacy from the Main Campus. There was an association between self-esteem and health literacy (p=0.007) but no association between sex, ethnicity, household income and year of study with health literacy. A greater focus on health in general as well as health literacy education intervention are appropriate to help improve undergraduates’ health literacy.